Modifikasi Laston AC-WC Menggunakan Limbah Bongkaran Beton - Heri Wahyudiono; Sudjati Sudjati; Budi Winarno; Ki Catur Budi (Universitas Islam Lamongan, 2020)
The use of raw materials as road pavement materials in general uses materials that are still fairly common. Researchers are trying to use alternative materials as substitutes for aggregates that are exploited continuously. This research uses fine aggregate demolished concrete that has been destroyed. The method used was an experiment with asphalt content variation of 6%, 6.5%, 7%, 7.5%, 8%. This test uses the Marshall method which is the basis for calculating the stability and flow values. In the Marshall test the results of testing the characteristics of the table the highest VMA value with asphalt 6% with a value of 19.87%, the highest VIM value with asphalt 6% with a value of 7.91 Highest VFB value with asphalt 6.5% with 89.62% stability value with asphalt 7% with 3538 kg value, for the highest flow value with optimum asphalt is at 7.5% and 8% of VIM, VMA, VFB values, STABILITY, and MQ.